Pembiayaan Berbasis Syariah pada Perusahaan Tanah Kavling CV. Anugrah Abadi Malang - Misbah, Ahmad; Fitriana Sari, Oktavia (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2022)
This study aims to identify the application of sharia principles in the financing carried out by CV. The Great Grace of Malang. One of the sharia-based financing is Murabaha financing, which is a buying and selling activity between land buyers and sellers, in this case CV. Malang Immortal Grace. The type of research used in this research is exploratory research. This research was conducted to investigate the application of murabaha financing practices in accordance with sharia principles at CV. Anugrah Abadi Malang, by conducting in-depth interviews with buyers/consumers of CV. Immortal Grace and Leaders and employees. In this study it was found that CV. Anugrah Abadi has carried out murabahah financing activities with reference to several sharia principles issued by the DSN MUI but still needs more intense understanding and assistance in an effort to realize the good intentions of the owner of CV. An eternal gift to avoid ribawi transactions.